Instructional Media Development Using Macromedia Flash In Blended Learning - Wahyudi, Wahyudi; Sundara, Tri Apriyanto; Candra, Afriando (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2016)
Operating system is a compulsory subject students STMIK Indonesia Padang. This course describes computers operating system for control and management of hardware and computer software. Computer operating system is located on the first layer of hard disk drive. When computer is turned on, software first work is operating system and other new applications are processed. The results of observations on STMIK Indonesia Padang, 30% of students have not been able to understand the subject of Operating System. Instructional media should be formulated so that material is easy to understand. The computer as a learning tool Operating System can be made interactive learning media applications. Many interactive CD Operating System in circulation, only contains general material and do not develop subject of discussion. Research objective of designing learning media Operating System using Macromedia Flash, which can be used as ingredients in learning process for students. The subjects were students STMIK Indonesia Padang subjects Operating Systems.